PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA ANGGOTA SATUAN RESERSE KRIMINAL POLRES WONOGIRI - pracelia, santa (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The purpose of this study was to analyze the significance effect of of leadership, work motivation and work discipline on the performance of the members of Criminal Investigation Unit Polres Wonogiri. This type of research is survey research. The study population consisted of 40 members of Criminal Investigation Unit Polres Wonogiri and the whole was used as a sample with population research techniques. The data source used primary data and secondary data. Data collection methods used questionnaires and literature study. Data analysis techniques used multiple linear regression. The results showed that leadership had a significant effect on performance of the members Criminal Investigation Unit Polres Wonogiri. Work motivation has a significant effect on performance of the members Criminal Investigation Unit Polres Wonogiri. Work discipline has a significant effect on performance of the members of Criminal Investigation Unit Polres Wonogiri. Keywords: leadership, work motivation, work discipline, performance